Economic, social and cultural rights - Ssenyonjo, Manisuli (Farnham, Surrey ; Burlington, VT : Ashgate, 2011)
"Economic, Social and Cultural Rights" is a collection of seminal papers examining legal, conceptual and practical questions regarding the international legal protection of economic, social and cultural rights. The volume discusses what human rights obligations economic, social and cultural rights entail for states and non-state actors; the nature and scope of substantive economic, social and cultural rights such as education, health, work, water, enjoyment of the benefits of scientific progress, and cultural rights; as well as the justiciability of these rights at an international level and at the national level. The paramount importance of such questions is illustrated, among other things, by the catastrophic situation of economic, social and cultural rights as human rights in developing and developed states. This volume is divided into three main parts which focus on human rights obligations for states and non-state actors arising from treaties protecting economic, social and cultural rights; analysis of selected substantive rights; and, finally the justiciability of economic, social and cultural rights in various contexts such as within the United Nations, Europe, Inter-American, and African systems, as well as within the domestic system.
Includes bibliographical references and index.
Keywords: International Covenant on Economic, Social, and Cultural Rights -- (1966); Human rights; Human rights -- Interpretation and construction; Social legislation; Due process of law; Judicial power